COLLECTION COSTS OF MURABAHAH FINANCING ACCORDINGS IN SHARIA ECONOMIC LAW COMPARATION IN SHARIA MAQASHID PERSPECTIVE - Yulianiva Maulida (Proceeding Of The International Seminar and Conference on Global Issues, 2020)
The contract is a written agreement that contains an agreement (offer) and qabul (acceptance) between one party and another party which contains rights and obligations between each party in accordance with sharia principles. reschedule murabahah bills for buyers who cannot pay in accordance with the agreed amount and time with the following conditions: do not add to the amount of the remaining invoice, charging fees in the rescheduling process are real costs, extension of the payment period must be based on the agreement of the parties. In this study discusses the concept provisions for billing fees for murabahah financing contracts in the compilation of sharia economic law and what are the rules for billing fees for murabahah financing contracts according to the maqashid sharia perspective. The method used in researching this issue is a type of library research. In this study, it is necessary for the authors to focus on the application of the compilation of Islamic economic law related to billing costs in murabaha contracts. From the results of the author's research on the provisions in Article 28 Paragraph (1) of the compilation of sharia economic law which reads that a valid contract is a contract that fulfills the pillars and conditions and if the obligation to pay the billing fee itself is not regulated, therefore, it may appear in later the billing fee with larger numbers, if this level of need is not met it will threaten human safety, so that the billing fee is not calculated clearly and is even greater than the profit margin of the contract, so the billing fee is not valid. Keywords: Billing Fees, Compilation of Sharia Economic Law, Maqashid Sharia.